Toilet hygiene in the classical era. (17th December 2012) - Charlier, Philippe; Brun, Luc; Prêtre, Clarisse; Huynh-Charlier, Isabelle
Abstract : Philippe Charlier and colleagues describe how the Romans wiped their bottoms and speculate about the resulting health problems